Minimally invasive treatment of infected pancreatic necrosis - Wroński, Marek; Cebulski, Włodzimierz; Słodkowski, Maciej; Krasnodębski, Ireneusz W. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Infected pancreatic necrosis is a challenging complication that worsens prognosis in acute pancreatitis. For years, open necrosectomy has been the mainstay treatment option in infected pancreatic necrosis, although surgical debridement still results in high morbidity and mortality rates. Recently, many reports on minimally invasive treatment in infected pancreatic necrosis have been published. This paper presents a review of minimally invasive techniques and attempts to define their role in the management of infected pancreatic necrosis.